Heterogeneous Bank Offerings against Homogeneous Customer Reflection - Raman, Arasu (Taiwan Institute of Business Administration, 2015)
While having the term “Islamic” banking, Malaysian banks operates their businesses using the rules and principles of Sharia’h. Due to the increase in housing development projects in Malaysia as a whole, the application of housing loan increases as well. As both conventional banks and Islamic banks offer housing loan products, some researchers pointed out those customers in Malaysia are satisfied with the housing loan provided by the Islamic banks while a few researchers commented that customers in Malaysia are not happy with the Islamic housing financing provided by the local banks. Therefore, this study aimed at discovering the influences of customer delight on Islamic housing loan in Malaysia. In this quantitative study, 250 questionnaires distributed to the respondents in the bank space. Out of which 220 valid feedbacks were collected hence factor analysis with reliability tests were conducted before using multiple regression for data analysis. The results pointed out that the service quality, product quality, and trusts are all delighting customers of Islamic housing loan in Malaysia in general context. The study validates the fact that customer satisfaction in general is homogeneous regardless to Islamic or conventional mode of offerings by the banks. Therefore, Malaysian banks when it comes to property financing should blend their marketing offering and keep the “Islamic” term of financing as a brand or mode as optional rather the only means.